Do Nuss bars compromise the blood flow of the internal mammary arteries? - YILDIZELİ, BEDRETTİN; BATIREL, HASAN FEVZİ; BOSTANCI, KORKUT; ERMERAK, NEZİH ONUR (OXFORD UNIV PRESS, 2013)
OBJECTIVES: Minimally invasive repair of pectus excavatum, the so-called Nuss procedure, has become a popular technique in recent years. The internal mammary arteries (IMAs) lie on the posterolateral surface of the sternum, and the Nuss bar is likely to obstruct the blood flow in these arteries. This obstruction could become important in the later stages of the lives of these young people if they were to require coronary artery bypass grafting. The goal of this study is to investigate the extent of obstruction of the IMAs caused by Nuss bars. METHODS: Data were collected prospectively on all patients who underwent the Nuss procedure between October 2011 and May 2012. Patients with a history of pectus excavatum repair by open surgery and those who were younger than 16 years of age were excluded. Computed tomography-angiography (CTA) was performed for the detection of IMA blood flow preoperatively and on the 10th postoperative day. Blood flow in the IMAs was evaluated blindly by two radiologists and classified as blood flow unaffected (group I) or affected (group II) by comparing the assessment of preoperative and postoperative CTAs. The patients in group II were also categorized as having blood flow obstructed bilaterally, blood flow obstructed unilaterally and others (diminished unilaterally/diminished on one side or obstructed on the other side). RESULTS: Thirty-four patients (31 male and three female; mean age 20.7 +/- 4.2 years) underwent surgery. Blood flow was affected in 15 patients (44%), with bilateral obstruction in five, unilateral obstruction in seven, and unilateral diminished flow in two patients. In one patient, blood flow was diminished on one side and obstructed on the other. There was no significant difference between unaffected group I patients and affected group II patients in terms of sex, age, type of deformity, Haller index and the number of bars placed. CONCLUSIONS: Nuss bars cause pressure on the IMAs, but a risk factor for this effect could not be identified. This is a relatively common clinical consequence of minimally invasive repair of pectus excavatum, and the long-term effects will be apparent following bar removal.
Keywords: Pectus excavatum; Chest wall deformity; Minimally invasive procedure; Internal mammary artery; Angiography; MINIMALLY INVASIVE REPAIR; LIFE-THREATENING COMPLICATION; PECTUS EXCAVATUM REPAIR; BYPASS GRAFTS